(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, in the conditions of the globalization of education, the pedagogical content of the development of intercultural communication competence in students, the development of intercultural communication competence in students is an urgent task, and the opinions are expressed to improve their knowledge and skills related to this competence.